Real Estate Agent Earnings and Local Housing Prices - Barry Hirsch; David A. Macpherson; Zichong (Tom) Qu (Institute of Labor Economics (IZA), 2022)
Real estate agents typically receive commissions based on a fixed percentage of home price purchases. Because housing prices vary across markets, one might expect that realtors have higher earnings in high-priced markets. Prior work by Hsieh and Moretti (2003) suggests that entry among realtors leads to roughly equivalent earnings across markets. We examine evidence from U.S. metro areas during 1996-2021 using Zillow housing price indices, coupled with realtor microdata (the CPS and ACS) including realtors' location, earnings, and work hours. Realtors' earnings elasticity with respect to local home prices is roughly 0.30, so that 10 percent higher home prices lead to 3 percent higher earnings. The positive wage-price relationship is not unique to realtors. The overall workforce has wage-price elasticities (conditioned on covariates) of about 0.20, two-thirds the size of realtors' elasticity. Realtors receive slightly higher earnings in higher-priced cities, about 1 percent for each 10 percent difference in housing prices. Weekly work hours across markets vary little with respect to metro housing prices, both for realtors and non-realtors. Evidence supports Hsieh and Moretti's conclusion that "over-entry" in high-priced markets is due to the inefficiency of fixed percentage commissions. Realtors have higher hourly earnings (and variance) than do "similar" non-realtor workers within the same labor markets, on the order of 10 percent. Evidence supports the view that real estate agents (on average) realize wage premiums. We suspect that higher earnings reflects both unmeasured personal attributes and compensating differentials for risk (e.g., variable earnings).
Keywords: J31; J44; R3; 330; wages; housing prices; real estate agents; wage differentials